The Students’ Entrance to Industry through Engineering Subjects: A Case of TVET College Campus at Vhembe District - Nduvazi Mabunda; Ramongwane Daniel Sephokgole; Moses Makgato; Jerald Hondonga (Journal of Education Technology, 2026)
Engineering subject instruction in Technical and Vocational Education and Training (TVET) colleges remains predominantly theory-oriented, limiting students’ readiness to enter industrial workplaces. Limited workplace practice, weak industrial collaboration, and insufficient access to authentic industrial tools hinder students’ opportunities to develop technical competence and industry-relevant employability skills. This study aimed to analyze the challenges affecting students’ entrance into industry through engineering subjects within TVET colleges, particularly in Report 191 programs in Limpopo Province, South Africa. A qualitative approach with a case study design was employed. Ten engineering lecturers were purposively selected from three TVET colleges. Data were collected through semi-structured interviews and classroom observations and analyzed using thematic analysis. Findings revealed that engineering instruction remained heavily classroom-centered, lacked meaningful industrial integration, and was constrained by inadequate facilities and limited lecturer industrial experience. Subjects such as engineering drawing, mathematics, power machines, and bricklaying required stronger implementation of practical learning and Work-Integrated Learning (WIL). The study highlights the importance of sustainable collaboration between TVET colleges and industries to strengthen practical competence, workplace readiness, and employability among engineering students.